Fetal urine biochemistry at 13–23 weeks of gestation in lower urinary tract obstruction: criteria for in‐utero treatment. (10th August 2015) - Abdennadher, W.; Chalouhi, G.; Dreux, S.; Rosenblatt, J.; Favre, R.; Guimiot, F.; Salomon, L. J.; Oury, J. F.; Ville, Y.; Muller, F.
ABSTRACT Objectives To assess the value of fetal urine biochemistry before 23 weeks of gestation in cases of lower urinary tract obstruction (LUTO) to refine prognosis and to select potential candidates for in‐utero intervention. Methods This was a retrospective study including 72 cases of LUTO with fetal urine sampled before 23 weeks and assayed for total protein, β‐2‐microglobulin, sodium, chloride, calcium, phosphorus, glucose and gamma‐glutamyl transpeptidase (GGTP). Two groups were defined according to renal outcome: 1) bilateral renal dysplasia on histological examination or renal failure at birth; 2) normal postnatal renal function or histologically normal appearance of the kidneys. Correlations between fetal urinary biochemical markers and postnatal renal function were studied. Results LUTO was isolated in 56/72 (77.8%) cases and was associated with other malformations in 16/72 (22.2%) cases. High GGTP levels (236 IU/L vs 5 IU/L; P < 0.0001) were observed in fetal urine in the five cases of urodigestive fistula. A significant difference between outcome groups was observed for β‐2‐microglobulin (P = 0.0017), sodium (P = 0.0008), chloride (P = 0.0028) and calcium (P = 0.0092) but not for protein, glucose or phosphorus. Sensitivity and specificity in defining a poor renal prognosis were 80.6% and 89% for β‐2‐microglobulin, 61.3% and 100% for sodium and 64.5% and 100% for calcium, respectively. Conclusions Fetal urinalysis before 23 weeks of gestation allowed distinction between three groups: 1) fetuses with normal urine biochemistry for which fetal therapy should be discussed; 2) fetuses with abnormal urine biochemistry for which prognosis for renal outcome is poor and for which the benefit of fetal therapy is likely to be compromised; 3) fetuses with urodigestive fistula. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.